Serum Neurofilament Light Chain Levels in Patients With Presymptomatic Multiple Sclerosis - Bjornevik, Kjetil; Munger, Kassandra L; Cortese, Marianna; Barro, Christian; Healy, Brian C; Niebuhr, David W; Scher, Ann I; Kuhle, Jens; Ascherio, Alberto (JAMA neurology, 2020)
Unrecognized demyelinating events often precede the clinical onset of multiple sclerosis (MS). Identification of these events at the time of occurrence would have implications for early diagnosis and the search of causal factors for the disease. To assess whether serum neurofilament light chain (sNfL) levels are elevated before the clinical MS onset. Nested case-control study among US military personnel who have serum samples stored in the US Department of Defense Serum Repository. Serum samples were collected from 2000 to 2011; sNfL assays and data analyses were performed from 2018 to 2019. We selected 60 case patients with MS who either had 2 samples collected before onset (mean follow-up, 6.3 years) or 1 sample collected before and 1 after onset (mean follow-up, 1.3 years), among 245 previously identified case patients. For each case, we randomly selected 1 of 2 previously identified control individuals matched by age, sex, race/ethnicity, and dates of sample collection. The sample size was chosen based on the available funding. Serum NfL concentrations measured using an ultrasensitive single-molecule array assay (Simoa). Log-transformed sNfL concentrations in case patients and control individuals compared using conditional logistic regression and linear mixed models. Mean age at baseline was 27.5 years, and 92 of 120 participants (76.7%) were men. Serum NfL levels were higher in case patients with MS compared with their matched control individuals in samples drawn a median of 6 years (range, 4-10 years) before the clinical onset (median, 16.7 pg/mL; interquartile range [IQR], 12.6-23.1 pg/mL vs 15.2 pg/m; IQR, 10.3-19.9 pg/mL; P = .04). This difference increased with decreasing time to the case clinical onset (estimated coefficient for interaction with time = 0.063; P = .008). A within-person increase in presymptomatic sNfL levels was associated with higher MS risk (rate ratio for ≥5 pg/mL increase, 7.50; 95% CI, 1.72-32.80). The clinical onset was associated with a marked increase in sNfL levels (median, 25.0; IQR, 17.1-41.3 vs 45.1; IQR, 27.0-102.7 pg/mL for presymptomatic and postonset MS samples; P = .009). The levels of sNfL were increased 6 years before the clinical MS onset, indicating that MS may have a prodromal phase lasting several years and that neuroaxonal damage occurs already during this phase.